A case-control study of deaths from asthma. Issue 11 (November 1986) - Rea, H H; Scragg, R; Jackson, R; Beaglehole, R; Fenwick, J; Sutherland, D C
Abstract : A population based case control-study was initiated in 1981 to identify risk factors for death from asthma. Over a two year period all deaths in the Auckland population possibly due to asthma, in people less than 60 years of age, were investigated. From the 47 people who died from asthma 44 who had useful reversibility of airways obstruction (records showing greater than 20% variability of peak flow or a history indicating equivalent variability of shortness of breath) before death were selected as cases for the study. Both hospital and community based controls were used. The cases were more likely than were the community controls to have had severe disease, a hospital admission or visits to a hospital emergency department in the previous year (odds ratios 4.4, 16.0, 8.5 respectively). The asthmatic patients who died were more likely than either group of controls to have had a previous life threatening asthma attack. Poor management of the disease and poor compliance on the part of the patient increased the risk of death. In addition, use of three or more types of asthma drug within the past year was associated with an increased risk of dying that was independent of disease severity. Of interest was a similarity between asthmatic patients admitted to hospital and those who died. Nevertheless, a history of a previous life threatening attack and a recent admission to hospital identified a group at high risk.